Navigating the Storm of COVID-19 Literature Through Academic-Practice Partnership in Washington State: The COVID-19 Literature Situation Report. Issue 1 (January 2022) - Simckes, Maayan; Shah, Anar; Guthrie, Brandon L.; Ross, Jennifer M.; Wasserheit, Judith; Wickersham, Kevin; Wasserman, Cathy
Abstract : Context: Shortly after the first COVID-19 case in the United States was identified in Washington, the Washington State Department of Health (WA DOH) determined that real-time knowledge of scientific findings related to SARS-CoV-2 was critical for an effective response. Epidemiologists at the WA DOH established the Daily Literature Situation Report (Lit Rep), within the agency's incident management team, to support public health and state leaders in evidence-based decision making. However, from January to May, the scale of the pandemic response and daily volume of emerging information grew beyond the capacity of the WA DOH epidemiology team tasked with gathering, reviewing, summarizing, and disseminating it daily. Objective: To ensure public health leaders maintained awareness of the rapidly evolving scientific literature during the pandemic to support evidence-based practice. Design: The WA DOH contracted the University of Washington (UW) Alliance for Pandemic Preparedness to assemble a team of faculty and students to continue producing the Lit Rep. Main Outcome: In addition to the daily Lit Rep, the UW team developed in-depth reports addressing questions from public health leadership and further evolved the methodology for the daily reports to support long-term sustainability and broader accessibility. Results: Throughout its existence, the Lit Rep had summarized more than 4300 articles from more than 150 000 citations and had more than 5600 subscribers from public health practice, academia, and the general public, both domestic and international. Conclusions: The flexible Lit Rep model sets a standard for responding to emerging public health threats and communicating complex scientific information to government leaders, public health staff, and other interested parties. The WA DOH and the UW have exemplified how a mutually beneficial partnership can be established to support more effective public health practice based on real-time evidence both during a crisis and potentially for future public health challenges. Abstract : Supplemental Digital Content is Available in the Text.